2009
DOI: 10.1002/cne.22286
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PTPRO in the interneurons of adult mouse olfactory bulb

Abstract: PTPRO is a receptor-type protein tyrosine phosphatase (PTP) with a single catalytic domain in its cytoplasmic region and multiple fibronectin type III-like domains in its extracellular region. In the chick, PTPRO mRNA has been shown to be particularly abundant in embryonic brain, and PTPRO is implicated in axon growth and guidance during embryonic development. However, the temporal and spatial expression of PTPRO protein in the mammalian CNS, particularly in the juvenile and adult mammalian brain, has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Rat mAbs to mouse SAP-1, to mouse PTPRO or to mouse VE-PTP were generated and prepared as previously described (Kotani et al 2009;Sadakata et al 2009;Mori et al 2010). A mouse mAb to phosphotyrosine (4G10) was from Millipore (Billerica, MA, USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat mAbs to mouse SAP-1, to mouse PTPRO or to mouse VE-PTP were generated and prepared as previously described (Kotani et al 2009;Sadakata et al 2009;Mori et al 2010). A mouse mAb to phosphotyrosine (4G10) was from Millipore (Billerica, MA, USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Expression vectors for mouse SAP-1, mouse VE-PTP and mouse PTPRO were generated as described (Kotani et al 2009;Sadakata et al 2009;Mori et al 2010). A full-length cDNA of mouse Grb2 was amplified by reverse transcriptionpolymerase chain reaction (RT-PCR) with total RNA from mouse brain (C57BL ⁄ 6) to construct an expression vector for Myc epitope-tagged Grb2.…”
Section: Plasmidsmentioning
confidence: 99%
“…It does not bind to calretinin and pre-adsorption of diluted antiserum with calbindin removed all the labeling in human brain (Huynh et al, 2000). Previous labeling of mouse olfactory bulb (Kotani et al, 2010), rat piriform cortex (Gavrilovici et al, 2010) and guinea pig enteric nervous system (Liu et al, 2005) all showed highly selective cytoplasmic labeling of neurons. We observed labeling consistent with previous reports.…”
mentioning
confidence: 96%